7.5k views
7 votes
Convert the following Logarithmic Equation into a Exponential Equation.

log_3(-2x+1)=-2y+6

1 Answer

1 vote

Answer:

The conversion is given by
3^(-2y+6) = -2x+1.

Explanation:

Logarithmic Equation to Exponential Equation:

To realize the conversion of a logarithmic equation to an exponential equation, we need to understand the meaning of a logarithim. We have that:


\log_(a) b = c

Means that:


b = a^c

We are given the following equation:


\log_(3) (-2x+1) = -2y + 6

It means that


3^(-2y+6) = -2x+1

Which is the conversion.

User Wolverdude
by
5.3k points